Disclosing antifungal activity of Huangqin decoction upon Trichophyton mentagrophytes and exploring its potential inhibitory mechanisms through transcriptome sequencing and qRT-PCR - Su-Qing Yang; You-Jin Ge; Cheng-Ying Shen (Scientific Reports)
Abstract Trichophyton mentagrophytes (T. mentagrophytes) is a prevalent pathogen that causes human and animal dermatophytosis. The clinical treatment of the infections is challenging due to the prolonged treatment duration, limited efficacy, antifungal resistance and side effects of existing drugs. Modern research has reported that the classic Traditional Chinese medicine (TCM) prescription Huangqin decoction (HQD) along with its principal ingredients could exhibit antifungal properties. Given the valued advantages of TCM such as broad-spectrum antifungal activity, low incidence of drug resistance and low toxicity, this study investigated the antifungal activity of HQD against T. mentagrophytes and explored the potential inhibitory mechanism, aimed to provide new clues for the treatment of dermatophytosis. By detecting minimal inhibitory concentration (MIC) using the broth microdilution method, the results showed that HQD could significantly inhibit the growth of T. mentagrophytes, with a minimal inhibitory concentration (MIC) of 3.13 mg/mL. The transcriptome sequencing and quantitative real-time PCR (qRT-PCR) technology were combined to shed light on the complicated adaptive responses of T. mentagrophytes upon HQD. The results demonstrated that at MIC, compared with the control group, a total of 730 differentially expressed genes (DEGs) were detected in T. mentagrophytes after HQD exposure (FDR adjusted p-value < 0.05), of which 547 were up-regulated and 183 were down-regulated. These DEGs were abundant in “single-organism metabolic process”, “catalytic activity” and “oxidoreductase activity”, and were significantly enriched in seven signaling pathways including glutathione metabolism, DNA replication, glyoxylate and dicarboxylate metabolism, taurine and hypotaurine metabolism, carotenoid biosynthesis, ubiquitin-mediated proteolysis, and cyanoamino acid metabolism. The results of transcriptome profiling were verified using qRT-PCR for a subset of 10 DEGs. The overall evidence indicated that HQD had a significant anti-dermatophyte activity and the adaptive responses of T. mentagrophytes upon HQD might be related to targeting glutathione S-transferase (GST) gene that could conjugate with toxic xenobiotics to defense oxidative stress, the inhibition of DNA replication pathway by downgrading the DNA replication licensing factors MCM3, MCM5 and ribonuclease H1 (RNaseH1) genes, and the repressed expression of phosphatidylserine decarboxylase (PSD) gene related to phospholipid synthesis which was indispensable for hyphal morphology, hyphal differentiation and cell wall integrity. Our study showed a new theoretical basis for the effective control of T. mentagrophytes infection and the effect of HQD on fungi, which are expected to offer aids for discovering new antifungal agents upon dermatophytosis.